AVEC 2017--Real-life depression, and affect recognition workshop and challenge - Ringeval, Fabien; Schuller, Björn; Valstar, Michel; Gratch, Jonathan; Cowie, Roddy; Scherer, Stefan; Mozgai, Sharon; Cummins, Nicholas; Schmitt, Maximilian; Pantic, Maja (2017)
The Audio/Visual Emotion Challenge and Workshop (AVEC 2017) “Real-life depression, and affect” will be the seventh competition event aimed at comparison of multimedia processing and machine learning methods for automatic audiovisual depression and emotion analysis, with all participants competing under strictly the same conditions. .e goal of the Challenge is to provide a common benchmark test set for multimodal information processing and to bring together the depression and emotion recognition communities, as well as the audiovisual processing communities, to compare the relative merits of the various approaches to depression and emotion recognition from real-life data. .is paper presents the novelties introduced this year, the challenge guidelines, the data used, and the performance of the baseline system on the two proposed tasks: dimensional emotion recognition (time and value-continuous), and dimensional depression estimation (value-continuous).